2020
DOI: 10.3389/fbioe.2019.00488
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of a Novel Endophytic Bacterium From Mulberry (Morus) Tree

Abstract: Mulberry (Morus) is an economically important woody tree that is suitable for use in sericulture as forage and in medicine. However, this broad-leaved tree is facing multiple threats ranging from phytopathogens to insect pests. Here, a Gram-positive, endospore-forming bacterium (ZJU1) was frequently isolated from healthy mulberry plants by screening for foliar endophytes showing antagonism against pathogens and pests. Whole-genome sequencing and annotation resulted in a genome size of 4.06 Mb and classified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…showed that the number of endophytic actinobacteria in cucumber ( Cucumis sativus L.) infected with Fusarium wilt was more than that in the root of healthy cucumber, and the endophytic strain HAAG3‐15 isolated from the root had strong antifungal ability against Fusarium wilt and broad‐spectrum antifungal activity. Bacillus amyloliquefaciens ZJU1 isolated from mulberry ( Morus alba L.) leaves can inhibit fungal diseases in mulberry trees, induce high expression of disease resistance genes in mulberry, and secrete secondary metabolites affecting growth and spore germination of B. cinerea and other fungal diseases 121 . An endophytic Burkholderia SSG isolated from Justin Brouwers boxwood ( Buxus sempervirens L.) leaves reduces incidence rate of 90% boxwood blight 122 .…”
Section: Endophytesmentioning
confidence: 99%
“…showed that the number of endophytic actinobacteria in cucumber ( Cucumis sativus L.) infected with Fusarium wilt was more than that in the root of healthy cucumber, and the endophytic strain HAAG3‐15 isolated from the root had strong antifungal ability against Fusarium wilt and broad‐spectrum antifungal activity. Bacillus amyloliquefaciens ZJU1 isolated from mulberry ( Morus alba L.) leaves can inhibit fungal diseases in mulberry trees, induce high expression of disease resistance genes in mulberry, and secrete secondary metabolites affecting growth and spore germination of B. cinerea and other fungal diseases 121 . An endophytic Burkholderia SSG isolated from Justin Brouwers boxwood ( Buxus sempervirens L.) leaves reduces incidence rate of 90% boxwood blight 122 .…”
Section: Endophytesmentioning
confidence: 99%
“…Endophytic bacteria play an important role in suppressing plant diseases ( 1 ). Bacillus amyloliquefaciens , a plant-associated bacterium, can be found in plant organs and exhibits antifungal activities against plant pathogens ( 2 4 ). Genome analysis helps to elucidate the gene clusters involved in the biosynthesis of active secondary metabolites of B. amyloliquefaciens ( 4 ).…”
Section: Announcementmentioning
confidence: 99%
“…Crop rotation is a slow method for reducing pathogen density in soil, making it unsuitable when severe disease breakout ( Chellemi et al, 2016 ). Biocontrol bacteria are receiving increasing attention as a potential alternative to traditional methods for controlling plant diseases ( Choi et al, 2020 ; Ogunnaike et al, 2021 ; Ahmed et al, 2022 ), based on being harmless, effective, and sustainable ( Xie et al, 2020 ). Previous studies have identified various biocontrol agents including Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%